THE CREATION OF A CONTEMPORARY PERFORMANCE “ACCEPT OR SURRENDER” - IAMKRASIN, SAKCHAI (Journal of Suan Sunandha Arts and Culture, 2023)
The purpose of this article is to create a contemporary performance The Creation of a Contemporary Performance “Accept or Surrender” for communicate about human adaptation to survive in a crisis “COVID-19” The creative work of art, this piece has brought scientific knowledge to apply the presentation method by using performing arts "Contemporary sword dance" and the use of The Semiotics Theory. In which the researcher studied and selected the concepts and methods of The Devising Theatre as follow; 1) Selection of issues in presentation. In which the researcher worked with the work piece advisor to select issues of interest and affecting awareness among viewer, in the matter of seriousness and protecting yourself from Corona virus. By selecting economic issues that people are struggling with falling incomes but increasing expenses. During the spread of the virus but has not received concrete talks to present in this work. 2) Opening up the listening space for use in creating presentations. The researcher provided space for both actors to participate in the design and creative presentation in their own perspective to create a sense of participation in the work example Contemporary sword dance with the application of martial arts by using the Traditional Thai sword through the movement of the symbol, which implies the meaning and compose gestures through acting in the form of Contemporary Dance Including the progression of the main characters (Plot) Designed in accordance with the real life context of both actors who are professionals, independent actors. The researcher created this performance in the form of short movies, that are no longer than 5 minutes in length and does not use any dialogue of the characters After that it has been publicized through the website www.youtube.com on the 26th of April 2020.